The Application of Pre-tensioned Grouted Tendons at Harworth Colliery, UK - Chris Adams (International Conference on Ground Control in Mining, 2003)
The application of pre-tensioned tendon roof support assisted Harworth Colliery in their revival, from impending closure to lowest cost deep-mined producer in the UK, over just six months last year. The paper describes this success story, how it came about, the reasons "why", and the method "how"